2005
DOI: 10.1016/j.cardiores.2005.01.026
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α regulates the mitochondrial antioxidant defense system in vascular endothelial cells

Abstract: These results unveil a novel regulatory pathway that links mitochondrial activity and mitochondrial oxidative stress protective systems. In addition, they suggest that PGC-1alpha could play a crucial protective role in vascular complications of diabetes, where the mitochondrial metabolism of glucose has been shown to result in oxidative stress and vascular endothelial cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
434
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(466 citation statements)
references
References 49 publications
20
434
0
2
Order By: Relevance
“…One possibility may involve the ability of PGC-1α, under some conditions, to activate genes that are implicated in the response to oxidative stress (34)(35)(36) and thus lead to a reduction of cellular oxidative stress levels. PGC-1α therefore may orchestrate the timely repression of HSPs in response to lower levels of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility may involve the ability of PGC-1α, under some conditions, to activate genes that are implicated in the response to oxidative stress (34)(35)(36) and thus lead to a reduction of cellular oxidative stress levels. PGC-1α therefore may orchestrate the timely repression of HSPs in response to lower levels of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…ROS production is proportional to the increase in mitochondrial respiration and electron transport chain activity (39). However, using muscle cells, it has been shown that PGC1α increases the expression of one of the major antioxidant enzymes of mitochondria, SOD2 (40)(41)(42). PGC1α is therefore able to upgrade aerobic energy metabolism while preserving ROS homeostasis by promoting ROS formation on one hand and ROS scavenging systems on the other.…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α has been shown to be a master regulator of mitochondrial biogenesis and cellular energy [43] , and powerfully suppresses reactive oxygen species (ROS) in vivo [32] . Furthermore, PGC-1α knockout mice are much more sensitive to damage by oxidative stress, displaying apoptotic cell death in the dopaminergic cells of the substantia nigra and in hippocampal neurons [32] .…”
Section: Discussionmentioning
confidence: 99%